Preparation and physical stability evaluation of palm oil-based nanoemulsion as a drug delivery system for propofol - Prasetyo, Bayu Eko; Norazrina Azmi; Ahmad Fuad Shamsuddin (Penerbit Universiti Kebangsaan Malaysia, 2018)
The objective of this study was to develop a formulation for propofol injection at various concentrations (1 and 2%) using palm oil-based nanoemulsion as the carrier. The nanoemulsions were characterised by globule size distribution (Dv 90 value), zeta potential, pH and viscosity determination. The physicochemical stability and accelerated stability of the formulations were also evaluated. Stability studies were performed for 6 months at 4, 16, 25 and 40oC storage temperatures. The propofol content was analysed by HPLC study. The characterisation result of propofol nanoemulsion 1 and 2% showed good globule size distributions in Dv 90 values of 284 ± 1.15 nm and 304 ± 1.20 nm and also stable zeta potential values of-43.37 ± 0.96 mV and -40.97 ± 1.36 mV, respectively. Accelerated test showed that the formulations have excellent stability with no physical changes observed after centrifugation, autoclaving at 121oC for 15 mins, shaking for 12 hours and thermal cycling test. The stability studies indicated that propofol emulsion show good stability for 6 months when stored at 4 ± 1oC and 16 ± 1oC based on Dv 90 values, zeta potential, and pH readings. No changes in propofol concentrations were observed after 6 months storage. Overall, propofol in palm oil-based nanoemulsions as carrier was found to be stable and can be used as an alternative anaesthetic injection.